2014
DOI: 10.1002/jcp.24563
|View full text |Cite
|
Sign up to set email alerts
|

Functional Role of Connexins and Pannexins in the Interaction Between Vascular and Nervous System

Abstract: The microvascular network of the microcirculation works in tight communication with surrounding tissues to control blood supply and exchange of solutes. In cerebral circulation, microvascular endothelial cells constitute a selective permeability barrier that controls the environment of parenchymal brain tissue, which is known as the blood-brain barrier (BBB). Connexin- and pannexin-formed channels (gap junctions and hemichannels) play a central role in the coordination of endothelial and smooth muscle cell fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 120 publications
(175 reference statements)
2
33
0
Order By: Relevance
“…Another possibility is that Px1 and Cx43 function in distinct localizations in brain capillary endothelial cells, e.g., Px1 on the luminal and/or abluminal membrane and Cx43 mainly in the gap junction regions. This is similar to the model proposed by Gaete et al (2014). In support of this notion, Px1 is localized on the plasma membrane of mouse inner retinal endothelial cells (Shestopalov and Panchin, 2008).…”
Section: Pannexin 1 and Connexin 43 In Human Brain Endothelial Cellssupporting
confidence: 89%
“…Another possibility is that Px1 and Cx43 function in distinct localizations in brain capillary endothelial cells, e.g., Px1 on the luminal and/or abluminal membrane and Cx43 mainly in the gap junction regions. This is similar to the model proposed by Gaete et al (2014). In support of this notion, Px1 is localized on the plasma membrane of mouse inner retinal endothelial cells (Shestopalov and Panchin, 2008).…”
Section: Pannexin 1 and Connexin 43 In Human Brain Endothelial Cellssupporting
confidence: 89%
“…In life, there is evidence that the astrocyte endfeet are strongly linked to the basal side of the endothelial cells by numerous such integrin-dystroglycan complexes, involving integrins in the endothelial basal cell membrane interacting with extracellular laminin and fibronectin, connecting collagen IV and proteoglycans in the extracellular space to dystroglycan inserted in the underlying astrocyte end feet membrane. Similarly, it is proposed that the astrocytic layer forms an effective 'second barrier' surrounding the endothelial tube, with connexin 43 gap junctions linking adjacent astrocyte endfeet [64], and the whole complex being sufficiently tightly knit to restrict ready entry of leukocytes and mast cells to the brain parenchyma except in pathological conditions [57]. It is also possible that matrix components of the basal lamina (e.g., specific laminin composition [158]) may play a more important role than has been appreciated [74], e.g., in restricting the entry of cells into the parenchyma after their migration across brain endothelial cells or the transfer of very large macromolecules (e.g., ~ 460 kDa ferritin [20]) from the ECS to the perivascular space for clearance.…”
Section: A Sieving Effect Of Perivascular Astrocyte Endfeet?mentioning
confidence: 99%
“…Clearly, more studies are needed before a consensus will be reached regarding involvement of Panx1 in alpha1-adrenergic receptor-mediated effects. It has also been suggested that release of calcitonin gene-related peptide (CGRP) from sensory-motor nerves can cause opening of Panx1 channels expressed by VSMCs in mouse mesenteric arteries [152]. However, as also noted by the authors, the physiological or pathophysiological relevance of CGRP-induced Panx1 channel opening remains to be determined [152].…”
Section: Pannexins In Resistance Arteries and Arteriolesmentioning
confidence: 88%
“…It has also been suggested that release of calcitonin gene-related peptide (CGRP) from sensory-motor nerves can cause opening of Panx1 channels expressed by VSMCs in mouse mesenteric arteries [152]. However, as also noted by the authors, the physiological or pathophysiological relevance of CGRP-induced Panx1 channel opening remains to be determined [152]. Finally, Panx2 is expressed in the middle cerebral artery [153], but whether this or the expression of Panx3 in very small arteries has functional consequences is unknown.…”
Section: Pannexins In Resistance Arteries and Arteriolesmentioning
confidence: 99%